SQL Query Design Patterns and Best Practices A Practical Guide to Writing Readable and Maintainable SQL Queries Using Its Design Patterns - Hughes, Steve; Neer, Dennis; Singh, Ram Babu; Mala, Shabbir H.; Andrews, Leslie; Zhang, Chi (Packt Publishing, 2023)
Enhance your SQL query writing skills to provide greater business value using advanced techniques such as common table expressions, window functions, and JSON Purchase of the print or Kindle book includes a free PDF eBook Key Features Examine query design and performance using query plans and indexes Solve business problems using advanced techniques such as common table expressions and window functions Use SQL in modern data platform solutions with JSON and Jupyter notebooks Book Description SQL has been the de facto standard when interacting with databases for decades and shows no signs of going away. Through the years, report developers or data wranglers have had to learn SQL on the fly to meet the business needs, so if you are someone who needs to write queries, SQL Query Design and Pattern Best Practices is for you. This book will guide you through making efficient SQL queries by reducing set sizes for effective results.
Keywords: SQL server; Database management; Client/server computing; SQL (Computer program language)